PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DI KELAS XI SMA NEGERI 1 ANGKOLA SELATAN - yulia pratiwi siregar (Institut Pendidikan Tapanuli Selatan, 2016)
This study originated from the low ability of communication mathematics of student of SMAN 1 Angkola Selatan. This study aimed to determine the effect use of cooperative learning model type Numbered Head Together (NHT) toward ability of communication mathematics of student.This research is Quasy Experiment. The population in this study were students of class 1th SMAN 1 Angkola Selatan. Techniques used in sampling is total sampling. The sample in this study were students of class X1 as an experimental class and student of class X2 as an control class. Research instrument in this study is test the ability of communication mathematics of student. Data were analyzed using mean aquality test that the t test. significant Taraf obtained was 0,666>0,05 which means the alternative hypothesis is accepted. That is, a significant difference between the type of cooperative learning model Numbered Head Together (NHT) toward ability of communication mathematics of student of SMAN 1 Angkola Selatan